MS‐based strategies for identification of protein SUMOylation modification. Issue 21 (27th June 2019) - Sheng, Zenghua; Wang, Xixi; Ma, Yanni; Zhang, Dan; Yang, Yanfang; Zhang, Peng; Zhu, Hongxia; Xu, Ningzhi; Liang, Shufang
Abstract: Protein SUMOylation modification conjugated with small ubiquitin‐like modifiers (SUMOs) is one kind of PTMs, which exerts comprehensive roles in cellular functions, including gene expression regulation, DNA repair, intracellular transport, stress responses, and tumorigenesis. With the development of the peptide enrichment approaches and MS technology, more than 6000 SUMOylated proteins and about 40 000 SUMO acceptor sites have been identified. In this review, we summarize several popular approaches that have been developed for the identification of SUMOylated proteins in human cells, and further compare their technical advantages and disadvantages. And we also introduce identification approaches of target proteins which are co‐modified by both SUMOylation and ubiquitylation. We highlight the emerging trends in the SUMOylation field as well. Especially, the advent of the clustered regularly interspaced short palindromic repeats/ Cas9 technique will facilitate the development of MS for SUMOylation identification.